الكلام البلاغي لعلم المعاني وفوائده في سورة الحاقة - Ahmad Nuruddin (Dirosatuna: Journal of Islamic Studies, 2022)
This study aims to know the rhetorical discourse of semantics and its benefits in Surat Al-Haqqa. The rhetorical speech is divided into the predicate, constructive, and predicate in Surat Al-Haaqah. The researcher found 34 primaries, requesting, negative, and constructive words in Surat Al-Haaqqa. The benefits of declarative and compositional speech consist of natural and rhetorical benefits. The problems discussed in this research are: 1) What are the types of rhetorical speech in Surat Al-Haqqah? 2) What are the benefits of rhetorical speech in Surat Al-Haqqah? The researcher used the research tools: observation, discussion, and analysis